HRM’s Role in ISO 9001 Implementation: Food & Beverages Case Study - Wiwin Nurcahyani; Apri Kuntariningsih; Samtono Samtono (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study investigates the role of human resource management (HRM) practices in implementing ISO 9001 quality management systems within food and beverage companies. Using a qualitative case study methodology with triangulation techniques, the research examined PT Pringsewu Cemerlang's ISO 9001 implementation through in-depth interviews, direct observations, and document analysis involving 32 informants across management, supervisory, and operational levels. The findings reveal that strategic HRM practices significantly enhance ISO 9001 implementation effectiveness, with overall service quality improving by 24.2%. Employee competency development emerged as the primary mediating mechanism, demonstrating 96.4% training completion rates and 76.8% job performance transfer effectiveness. Training and development (4.2/5.0) and communication systems (4.1/5.0) proved most impactful in facilitating quality improvements across reliability (35.5% improvement), responsiveness (21.2%), and comfort/assurance (17.1%) dimensions. The study identifies three critical integration mechanisms: (1) standardization of work procedures and customer service protocols, (2) systematic competency development aligned with ISO 9001 requirements, and (3) enhanced communication systems supporting organizational change. However, persistent challenges include employee resistance (32.4%) and cross-branch consistency issues (22.1%), highlighting the importance of cultural transformation in quality management success. Theoretical contributions extend the resource-based view of strategic HRM by demonstrating how human capital resources generate competitive advantage through quality management integration. Practical implications provide actionable frameworks for food and beverage companies seeking to leverage HRM practices for sustainable quality improvements. The research challenges previous skepticism regarding ISO 9001's tangible benefits by showing how effective human resource management unlocks operational improvement potential in industry contexts.